Melatonin ameliorates anxiety and depression‐like behaviors and modulates proteomic changes in triple transgenic mice of Alzheimer's disease. (13th June 2017) - Nie, Lulin; Wei, Gang; Peng, Shengming; Qu, Zhongsen; Yang, Ying; Yang, Qian; Huang, Xinfeng; Liu, Jianjun; Zhuang, Zhixiong; Yang, Xifei
Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative disease accompanied by neuropsychiatric symptoms, such as anxiety and depression. The levels of melatonin decrease in brains of AD patients. The potential effect of melatonin on anxiety and depression behaviors in AD and the underlying mechanisms remain unclear. In this study, we treated 10‐month‐old triple transgenic mice of AD (3xTg‐AD) with melatonin (10 mg/kg body weight/day) for 1 month and explored the effects of melatonin on anxiety and depression‐like behaviors in 3xTg‐AD mice and the protein expression of hippocampal tissues. The behavioral test showed that melatonin ameliorated anxiety and depression‐like behaviors of 3xTg‐AD mice as measured by open field test, elevated plus maze test, forced swimming test, and tail suspension test. By carrying out two‐dimensional fluorescence difference gel electrophoresis (2D‐DIGE) coupled with mass spectrometry, we revealed a total of 46 differentially expressed proteins in hippocampus between the wild‐type (WT) mice and non‐treated 3xTg‐AD mice. A total of 21 differentially expressed proteins were revealed in hippocampus between melatonin‐treated and non‐treated 3xTg‐AD mice. Among these differentially expressed proteins, glutathione S‐transferase P 1 (GSTP1) (an anxiety‐associated protein) and complexin‐1 (CPLX1) (a depression‐associated protein) were significantly down‐regulated in hippocampus of 3xTg‐AD mice compared with the WT mice. The expression of these two proteins was modulated by melatonin treatment. Our study suggested that melatonin could be used as a potential candidate drug to improve the neuropsychiatric behaviors in AD via modulating the expression of the proteins (i.e. GSTP1 and CPLX1) involved in anxiety and depression behaviors. © 2017 BioFactors, 43(4):593–611, 2017